Pengaruh Current Ratio, Total Asset Turnover, Dan Debt To Total Asset Terhadap Return On Asset Pada Perusahaan LQ45 Di Bursa Efek Indonesia Periode 2011-2013 - Angela, Maya; Widayanti, Rita; Colline, Fredella (Ilmiah Manajemen Bisnis, 2015)
ABSTRACTThe purpose of this research is to help investors in making decision how to invest in the stock market by analyzing the influences of liquidity, activity, and solvency ratio on companyÃ¢â¬â¢s profitability. Financial rations which are used in this research are Current Ration, Total Asset Turnover, and Debt to Total Asset as independent variables and Return On Assets as the dependent variable. This research is using the purposive sampling method with 17 sample of LQ45 companies which fulfilled the research criteria during the period 2011-2013 from 45 existing listed companies. This research is using the Multiple Linear Regression Analysis, Classical Assumption Test, and Hypothesis Testing. Based on Classical Assumption Test results prove that the data which are used in this research do not have any problem of normality, multicollinearity, autocorrelation, and heteroscedasticity. The results of Partial Hypothesis Testing show that Current Ratio has a significant positive influence on Return On Asset, Total Asset Turnover has a significant positive influence on Return On Asset, and Debt to Total Assets does not have any significant influence on Return On Asset. If Current Ratio increases, Return On Asset will decreases. If Total Asset Turnover increases, Return On Asset will also increases. Instead, the changes in the Debt to Total Asset has no impact on Return On Asset changes.Keywords: current ratio, total asset turnover, debt to total asset, return on assetABSTRACTPenelitian ini bertujuan untuk membantu para investor dalam pengambilan keputusan bagaimana melakukan investasi di pasar modal dengan menganalisis pengaruh rasio likuiditas, aktivitas, dan solvabilitas terhadap profitabilitas perusahaan. Rasio keuangan yang digunakan dalam penelitian ini antara lain, yaitu Current Ratio (X1), Total Asset Turnover (X2), dan Debt to Total Asset (X3) yang digunakan sebagai variable independen dan Return On Asset (Y) sebagai variable dependen, Penelitian ini menggunakan teknik pengambilan sampel purposive sampling dengan sampel sebanyak 17 emiten LQ45 yang memenuhi kriteria penelitian selama periode tahun 2011-2013 dari 45 emiten yang ada. Penelitian ini menggunakan Analisis Regresi Linear Berganda, Uji Asumsi Klasik, dan Pengujian Hipotesis. Berdasarkan hasil Uji Asumsi Klasik terbukti bahwa data yang digunakan dalam penelitian ini tidak memiliki masalah normalitas, multikolinieritas, autokolerasi, dan heteroskedastisitas. Hasil dari pengujian hipotesis secara parsial menunjukkan bahwa Current Ratio memiliki pengaruh negarif yang signifikan terhadap Return On Asset, Total Asset Turnover memiliki pengaruh positif yang signifikan terhadap Return On Asset, dan Debt to Total Asset tidak memiliki pengaruh signigfikan terhadap Return On Asset. Dengan demikian, dapat disimpulkan bahwa hanya variable Current Ratio dan Total Asset Turnover yang memiliki pengaruh terhadap Return On Asset. Semakin besar Current Ratio, maka Return On Asset akan semakin kecil. Semakin besar Total Asset Turnover, maka Return juga akan semakin besar. Sedangkan perubahan Debt to Total Asset tidak berdampak terhadap perubahan Return On Asset.Keywords: current ratio, total asset turnover, debt to total asset, return on asset